The Roads to Congress 2020
XXII, 334 p. 14 illus., 8 illus. in color.
Keywords: This book analyzes changes to campaigning and voting in the United States in 2020. The global pandemic caused by COVID-19 upended traditional campaign strategies, posed unprecedented challenges to candidates, and possessed the potential to fundamentally alter how campaigns think about running for office. At the same time, the Trump administration’s divisive handling of twin crises stemming from the pandemic and rising racial tensions loomed over congressional races as the most disruptive election cycle in living memory. The ramifications of the 2020 congressional elections for the direction of public policy in America—and perhaps for American democracy itself—cannot be overstated. The Roads to Congress 2020 examines key House and Senate campaigns, candidates, and controversies in the 2020 election to reveal what accounts for the outcomes and point the way to America’s political future. Sean D. Foreman is Professor of Political Science at Barry University, USA. Marcia L. Godwin is Professor of Public Administration at the University of La Verne, USA. Walter Clark Wilson is Associate Professor of Political Science at the University of Texas at San Antonio, USA.